Programa educativo "cuidemos nuestro ambiente" y el desarrollo de la actitud ambiental de los niños de educación primaria de la institución educativa pedro m. ureña de la ciudad de Trujillo - Tejada Castañeda, Hugo Raúl (2016)
The goal of the realization of the research program entitled "Care for Our Environment" and the Development of Environmental Attitudes of primary school children of School Peter M. Ureña "in the city of Trujillo, was to demonstrate that the development program would help develop environmental attitudes in the selected sample. For its implementation was counted with a population comprised of 108 children in the third grade of primary school, and a sample of 30 third graders "E" representing a sample of already formed groups or intact, which constituted one workgroup pretest and posttest with the characteristics of a quasi-experimental research. The methodology used was experimental in nature, with the development of a stimulus consisting of the "take care of our environment," developing experiential activities, conducting ongoing observation of children's behavior in case of feedback, as well as the active participation of children in performing activities. As a result of the development of the program, important information was obtained in all three dimensions assessed: cognitive dimension, dimension and conative attitudinal dimension; finding significant differences between pretest and postetst, so it was concluded that the program "Care for our environment" has significantly influenced the development of environmental attitudes of children in the third grade "E" EI No 81014,. "Peter M. Ureña."